ANALISIS KELAYAKAN USAHA BUDIDAYA APEL (STUDI KASUS DI DESA BUMI AJI KECAMATAN BUMI AJI KOTA BATU - Budiman, Eko Wahyu; Sudibyo, Rahmad Pulung; Baroh, Istis (Viabel : Jurnal Ilmiah Ilmu-Ilmu Pertanian, 2018)
Technological developments have brought apple commodities into business commodities that can improve the well-being of the actors involved, as well as highly selective apple plants, can only grow well and well in certain areas of East Java, such as Batu and Nongkojajar. Data analysis method using Quantitative Descriptive analysis to know the level of financial feasibility of business, calculated by analysis of Acceptance and Cost (B / C ratio), Internal Rate of Return (IRR), Net Present Value (NPV), and Payback Period (PP). As for the marketing aspect using qualitative descriptive analysis. Based on research conducted in Bumiaji Village, Bumiaji Subdistrict of Malang City, that cultivation of apple is feasible to be cultivated with NPV of Rp. 471,825,898, - using the current bank interest of 12%, and also for Gross B / C ratio of 2.4633, Net B / C ratio of 4.6088, while IRR of 34.43%. As for the refund cost incurred taken from the amount of Net Benefit in the 4th year until the 13th year that is Rp. 1.129.796.500. so that in the 14th to the 26th year there is a net profit of a total of Rp 1,270,351,050, -.